BODY IMAGE AND SELF CONFIDENCE AMONG PREGNANT WOMEN: A CROSS SECTIONAL STUDY IN RURAL INDONESIA - Risa Putri Utami; Eko Mardiyaningsih (Universitas Nahdlatul Ulama Surabaya, 2026)
Background: Pregnancy in the second and third trimesters involves significant physical changes and psychological adjustments that may influence women’s perceptions of their bodies and their level of self-confidence. Purpose: This study aimed to examine the relationship between body image and self-confidence among pregnant women in the second and third trimesters in Sumogawe Village, Getasan District. Methods: A quantitative correlational design with a cross-sectional approach was applied. A total of 56 pregnant women were selected using purposive sampling. Body image was assessed using the Body Image Scale, while self-confidence was measured using the Self-Confidence Scale based on Lauster’s concept. Data were collected online through Google Forms with coordination from the village midwife and analyzed using univariate analysis and the Spearman Rank correlation test. Results: The results showed that most respondents had a positive body image (57.1%), while 42.9% reported a negative body image. In terms of self-confidence, 57.1% of respondents had low self-confidence and 42.9% had high self-confidence. Statistical analysis revealed a strong, positive, and significant relationship between body image and self-confidence (Spearman’s ρ = 0.727; p < 0.001), indicating that a more positive body image is associated with higher self-confidence. Conclusions: Body image is an important factor related to self-confidence among pregnant women and reflects psychological adaptation during pregnancy. These findings highlight the need to integrate psychosocial assessment and support, particularly related to body image and self-confidence, into routine antenatal care to promote maternal well-being.